(Study on Stomach Contents of Opudi Fish (Telmatherina celebensis) in Towuti Lake, South Sulawesi) - Sulistiono, .; Furkon, A.; Affandi, R. (Indonesian Society of Scientific Aquaculture (ISSA), 2006)
Study on food habits of opudi fish (T. celebensis) was conducted in Towuti Lake, South Sulawesi, from October 2002 to April 2003. The objective of this study was to investigate food habits of the fish. Samples were collected by using experimental gill net, mesh size 0,75; 1; 1,25 and 1,5 inches. The fish (N=273) was consisted of 141 males and 132 females, varied in total body length (55.8-94.7 mm). Stomach content was analyzed using Index of preponderance. Stomach contents of the fish was consisted of 4 kinds of foods such as insect, part of organism, debris and zooplankton. Main food of the fish was insect (IP 51.22% for male, 43.26% for female, suplement food was part of insect (IP 26.99% for male, 30.27% for female) and debris (IP 14.06% for male, 15.83% for female), while additional food was zooplankton consisted of Closterium (IP 2.93% for male, 4.62% for female), Pinnularia (IP1.79% for male, IP 1.39% for female), Navicula (IP 1.19%, for male, 1.41% for female) and Nitzschia (IP 0.74% for male, 1.08% for female). Food kind between male and female fish was similar. Keywords : Stomach contents, opudi fish (T.celebensis), Towuti Lake. ABSTRAK Penelitian makanan ikan opudi (T.celebensis) dilakukan di Danau Towuti, Sulawesi Selatan pada bulan Oktober 2002-April 2003. Tujuan dari penelitian ini adalah untuk mengetahui isi lambung ikan opudi. Ikan contoh diambil dengan experimental gill net dengan ukuran mata jaring 0,75; 1; 1,25 dan 1,5 inchi. Ikan yang tertangkap (N=273) terdiri atas Jantan (141) dan betina (132), yang memiliki variasi ukuran panjang tubuh (55,8-94,7 mm). Isi lambung dianalisis dengan menggunakan Index of preponderance (IP). Isi lambung terdiri dari 4 jenis makanan yaitu insekta, potongan tubuh insekta, serasah dan zooplankton. Makanan utama ikan opudi adalah insekta (IP 51,22% untuk jantan, 43,26% untuk betina), makanan pelengkap adalah potongan insekta (IP 26,99% untuk jantan, 30,27% untuk betina) dan serasah (IP 14,06% untuk jantan, 15,83% untuk betina), sedangkan makanan tambahan berupa zooplankton yang terdiri atas Closterium (2,93% untuk jantan, 4,62% untuk betina), Pinnularia (1,79% untuk jantan, 1,39% untuk betina), Navicula (1,19% untuk jantan, 1,41% untuk betina) and Nitzschia (0,74% untuk jantan, 1,08% untuk betina). Berdasarkan indeks similaritas, jenis makanan untuk ikan jantan dan ikan betina adalah mirip. Kata kunci : Isi lambung, ikan opudi (T.celebensis), Danau Towuti.